Customers' Preference of Online Marketplace: Trendyol and Hepsiburada Case Study - Kemora, Haura; Pasaribu, Popy Novita (Jurnal Manajemen, 2023)
The development of internet has increased the popularity of e-commerce. There are many different types of online marketplace, and each of them has its own customer base. Customers develop their preference or choice of specific online marketplace over the competitors. This research aimed to understand the factors influencing the choice. The research explored online dimensions that influencing user experience during shopping. In addition, the research incorporates neuroscientific findings, namely limbic types which is essentially similar to customer persona. Analysis of customer persona of the limbic type used descriptive analysis and dimension of attitude online shopping used regression analysis that done with SPSS application. The object of research was the online shopper with marketplace Trendyol and Hepsi Burada. The sampling technique was purposive with the criteria of responden is online shoppers. The collection of data by google form used snowballing technique. The total respondents were 117. The results showed that Trendyol type of limbic types ware Connoisseurs and Hedonist. The limbic map of Trendyol was Fantasy/Pleasure towards Balance System. The dimensions of brand identity that give significant effect were interactivity, information quality, usability, entertainment and personalization. Interactivity, usability and entertainment gave a positive and significant effect towards brand attitude formation in E-shops Trendyol or Hepsiburada, whereas information quality and personalization resulted on signicantly negative impact. Design and domain name had no significant effect towards dependent variable. The model could explain 79.2% of brand attitude formation in E-shops Trendyol or Hepsiburada